Chapter Dinamiche della disuguaglianza economica nella Repubblica di Venezia: fonti e metodi d'indagine a partire dal caso padovano - DI TULLIO, MATTEO (Datini Studies in Economic History, 2020)
This paper presents an analysis of the available primary sources and the existing methods to reconstruct the tendencies of the economic inequality in the Venetian Mainland, focusing on the case of Padua and its province, the so called contado. After presenting briefly the evolution of the administrative and fiscal system of the Republic of Venice, this paper analyses the main characteristics of the fiscal primary sources produced in the Padovano and proposes a synthetic analysis of the economic inequality trends in this province.